1998
DOI: 10.1016/s0042-6989(97)00464-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of the primary visual cortex in higher level vision

Abstract: In the classical feed-forward, modular view of visual processing, the primary visual cortex (area V1) is a module that serves to extract local features such as edges and bars. Representation and recognition of objects are thought to be functions of higher extrastriate cortical areas. This paper presents neurophysiological data that show the later part of V1 neurons' responses reflecting higher order perceptual computations related to Ullman's (Cognition 1984; 18:97-159) visual routines and Marr's (Vision NJ: F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
313
6
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 471 publications
(366 citation statements)
references
References 57 publications
46
313
6
1
Order By: Relevance
“…In contrast, the present data from anesthetized animals demonstrated clear modulation by nearby texture borders, but did not confirm the figural "interior enhancement" effects reported in the studies on alert animals (Lamme, 1995;Zipser et al, 1996;Lee et al, 1998). Only the recent alert monkey study of Lee et al (1998) distinguished between enhancement effects observed near texture boundaries and those related to the size and form of texture figures. In that study, texture border enhancement effects were most pronounced when the border was parallel to the cell's preferred orientation.…”
Section: Figure and Groundcontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast, the present data from anesthetized animals demonstrated clear modulation by nearby texture borders, but did not confirm the figural "interior enhancement" effects reported in the studies on alert animals (Lamme, 1995;Zipser et al, 1996;Lee et al, 1998). Only the recent alert monkey study of Lee et al (1998) distinguished between enhancement effects observed near texture boundaries and those related to the size and form of texture figures. In that study, texture border enhancement effects were most pronounced when the border was parallel to the cell's preferred orientation.…”
Section: Figure and Groundcontrasting
confidence: 99%
“…4 and 5 were based mainly on texture edges; only a few cells were tested exclusively with texture bars. However, a recent report suggested that texture responses can depend on the shape or size of the texture field and that figural and non-figure edges might produce different effects (Lee et al, 1998). We therefore compared the responses to texture edges and texture bars in 15 cells.…”
Section: Edges Vs Barsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurophysiologically, a role for MT/MST in Wgure/ground assignment for structure-from-motion has been suggested for the past two decades (Allman et al 1985;Olavarria et al 1992;Eifuku and Wurtz 1999;Born 2000;Born and Bradley 2005). Rapid feedback to V1 from areas with large receptive Welds, such as V2 or MT, was proposed in many cases Lamme 1995;Zipser et al 1996;Lee et al 1998;Nothdurft et al 1999Nothdurft et al , 2000Hup茅 et al 2001;Craft et al 2007). The connections between V1 and MT were found to conduct at the high speed of 禄10 m/s Wiesel 1983, 1989;Born and Tootell 1991;DeAngelis et al 1994;Grinvald et al 1994;Fitzpatrick 2000;Anderson et al 2001;Girard et al 2001;Bair et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Kimia [17] provides a comprehensive discussion of the possible role of medial geometry in the human visual system. Neurophysiological experiments by Lee et al [19], [20] observed peak neural activity in the V1 cells at localities of medial axis and psychophysical experiments such as those by Kovacs [18] suggest that medial points may be used in encoding shape information.…”
Section: Introductionmentioning
confidence: 99%